Determinanti relazionali e sopravvivenza delle imprese familiari in contesti sfavorevoli: un’analisi qualitativa - Cabiddu, Francesca; Pettinao, Daniela (Piccola Impresa / Small Business, 2008)
This paper proposes to examine the analyses of the determinants involved in the success of family run businesses. Among the numerous factors which influence the development of such businesses, attention is drawn to the specific importance of the synergy which these businesses create within their area of operation to their survival and success. In particular, the objective of this paper is to demonstrate that the diffusion and consolidation of stable and long term relationships between the business and local structures favour not only the achievement of positive performance on the part of the business, but the overcoming of limits derived from working in unfavourable contexts.